2020
DOI: 10.3390/nano10030405
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanism of Nano-SiO2 for Improving the Properties of Cement-Based Soil Stabilizer

Abstract: A new nano-soil stabilizer (N-MBER, Nanometer Material Becoming Earth into Rock) material was developed in this research by using the high activity and ultrafine properties of nano-SiO2 (NS), which were able to improve the properties of cement-based soil stabilizer and had broad application prospects. The results showed that (1) the strength of N-MBER obeyed a compound function relation with curing period and additive amount of NS. The relationship between strength and curing period obeyed an exponential funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In other words, the NSS stress–strain curve roughly demonstrated geometric characteristics of an “S” shape in the ascending stage before the NSS arrived at the peak stress, which showed high geometric similarity with a “logistic” curve from the perspective of the variation trend. Accordingly, combined with the research results of the strength growth model of N-MBER, the “S-Logistic” growth function model could be used to simulate the ascending stage of the NSS stress–strain curve [ 3 , 40 ], where the stress increased slowly and showed an exponential trend in the initial stage, then increased rapidly within a certain range, and finally the growth rate gradually decreased again. The function model is shown in Equation (4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the NSS stress–strain curve roughly demonstrated geometric characteristics of an “S” shape in the ascending stage before the NSS arrived at the peak stress, which showed high geometric similarity with a “logistic” curve from the perspective of the variation trend. Accordingly, combined with the research results of the strength growth model of N-MBER, the “S-Logistic” growth function model could be used to simulate the ascending stage of the NSS stress–strain curve [ 3 , 40 ], where the stress increased slowly and showed an exponential trend in the initial stage, then increased rapidly within a certain range, and finally the growth rate gradually decreased again. The function model is shown in Equation (4).…”
Section: Resultsmentioning
confidence: 99%
“…As a new green material for the efficient utilization of soil and water resources, the soil nano-stabilizer was developed innovatively on the basis of traditional cement-based soil stabilizers [ 1 , 2 , 3 ]. It can not only improve the micro interface structure and macro mechanical properties of normal soil at room temperature [ 4 ] but also possesses the characteristics of high strength, strong durability and a simple preparation process.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it may increase the unconfined compressive and shear strengths of the expansive soil [28]. Zhang [30] investigated the impact of the NS content on soil strength by establishing the relationship between the NS content and soil strength. However, the price of nanosilica is high, and the direct use of NS for improvement will result in high engineering costs.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the optimal quantity of SiO 2 can significantly enhance both the hydraulic conductivity and compressive strength of cemented soil [5]. The highly reactive nano-SiO 2 can efficiently catalyze the formation of calcium silicate hydrate gels (C-S-H) and facilitate their uniform dispersion [6]. Using nano-magnesia-cement, the cured seashore soft soil had a significant increase in shear strength and shear modulus [7].…”
Section: Introductionmentioning
confidence: 99%